2005
DOI: 10.2337/diacare.28.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Resistance Training Is Not Sufficient to Maintain Improved Glycemic Control Following Supervised Training in Older Individuals With Type 2 Diabetes

Abstract: OBJECTIVE -To examine whether improvements in glycemic control and body composition resulting from 6 months of supervised high-intensity progressive resistance training could be maintained after an additional 6 months of home-based resistance training.RESEARCH DESIGN AND METHODS -We performed a 12-month randomized controlled trial in 36 sedentary, overweight men and women with type 2 diabetes (aged 60 -80 years) who were randomly assigned to moderate weight loss plus high-intensity progressive resistance train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
138
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(152 citation statements)
references
References 18 publications
8
138
0
3
Order By: Relevance
“…Of the two previous studies 10,11 that have investigated the benefits of home-based RT in patients with type 2 diabetes, both used dumbbells and/or ankle weights to provide the training stimulus. This type of equipment makes it difficult to perform moderate-to highintensity RT using multijoint, large muscle exercises and may explain why these studies reported that home-based training was insufficient to further increase strength or maintain improvements in A1C following a period of supervised laboratory-based RT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the two previous studies 10,11 that have investigated the benefits of home-based RT in patients with type 2 diabetes, both used dumbbells and/or ankle weights to provide the training stimulus. This type of equipment makes it difficult to perform moderate-to highintensity RT using multijoint, large muscle exercises and may explain why these studies reported that home-based training was insufficient to further increase strength or maintain improvements in A1C following a period of supervised laboratory-based RT.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only two studies have examined the effectiveness of performing RT with the type 2 diabetes population in a home-based setting, 10,11 and both used home-/community-based RT to try and maintain improvements in glycemic control after an initial laboratory-supervised RT program. In both studies, home-based training was ineffective for maintaining the improvements in glycemic control and insulin sensitivity observed with the more rigorous laboratory-based program.…”
Section: Introductionmentioning
confidence: 99%
“…In both studies, the average age of participants was 66 years, and the resistance-training regimen involved multiple exercises at high intensity (three sets, three times per week), and absolute A1C declined 1.1-1.2% in resistance-training subjects versus no significant change in control subjects. One of these trials had a second phase (months 7-12), where training was home based rather than facility based (34). Body composition changes were maintained, but exercise intensity and adherence were lower than in the first 6 months and the A1C difference between groups became statistically nonsignificant.…”
Section: Resistance Trainingmentioning
confidence: 99%
“…11 High intensity resistance training may provide equal or greater metabolic benefit than other forms of exercises. 14 Virtually no study of isolated low intensity PRT shows change in adiposity or improved insulin sensitivity, 15 whereas high-intensity PRT has been shown to reduce visceral fat, 5 glucose control and insulin resistance 6,7 in obese and diabetic adults. 16 Position statements from numerous national organizations now advocate the use of supervised resistance training with children and adolescents.…”
Section: Introductionmentioning
confidence: 99%